Physicochemical Characteristics of Breadfruit (Artocarpus altilis) Starch Based on Starch Preparation and Modification Methods - Santi Noviasari; Yefa Hafiza Rahma; Cut Nilda (Food ScienTech Journal, 2024)
Breadfruit (Artocarpus altilis) is a starchy and nutritious food, particularly in carbohydrates. Breadfruit can be turned into starch to increase its usefulness and shelf life. The purpose of the study was to evaluate how different starch preparation and modification procedures affected the physical and chemical properties of the final starch. This study applied a factorial Randomized Block Design (RBD) approach, namely starch preparation (porridge and chips) and modification methods (heat moisture treatment/HMT, acetic acid immersion, and autoclaving-cooling). The overall yield, starch content, air content, ash content, amylose content, swelling power, solubility, and clarity were all examined. Data is processed using Analysis of Variance (ANOVA) in the SPSS application version 21, and if there are any differences between treatments, a Duncan Multiple Range Test (DMRT) will be performed. This study examined different techniques of starch preparation and modification methods that affected the properties of breadfruit starch. Breadfruit starch produced using the autoclaving-cooling modified porridge method had the best characteristics, with a total yield of 10.81%, starch content of 86.73%, water content of 9.59%, ash content of 0.42%, amylose content of 24.18%, swelling power of 9.02 g/g, solubility 8.93%, and paste clarity 71.86%T.